O lixo nosso de cada dia - Barboza, Irany Aparecida Ferreira da Cunha; Okazaki, Maria Silva Guimarães; Domingos, Maria Aparecida; Lima, Eliene Xavier de; Alcione (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf